Emerging influence of RNA post-transcriptional modifications in the synovial homeostasis of rheumatoid arthritis - Fatima, Madiha; Huang, Fengmei; Fu, Xiaohong (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is an important autoimmune disease that affects synovial tissues, accompanied by redness, pain, and swelling as main symptoms, which will limit the quality of daily life and even cause disability. Multiple coupling effects among the various cells in the synovial micro-environment modulate the poor progression and development of diseases. Respectively, synovium is the primary target tissue of inflammatory articular pathologies; synovial hyperplasia, and excessive accumulation of immune cells lead to joint remodelling and destroyed function. In general, epigenetic modification is an effective strategy to regulate dynamic balance of synovial homeostasis. Several typical post-transcriptional changes in cellular RNA can control the post-transcriptional modification of RNA structure. It can inhibit important processes, including degradation of RNA and nuclear translocation. Recent studies have found that RNA modification regulates the homeostasis of the synovial micro-environment and forms an intricate network in the “bone-cartilage-synovium” feedback loop. Aberrant regulation of RNA methylation triggers the pathological development of RA. Collectively, this review summarises recent advanced research about RNA modification in modulating synovial homeostasis by making close interaction among resident synovial macrophages, fibroblasts, T cells, and B cells, which could display the dramatic role of RNA modifications in RA pathophysiological process and perform the promising therapeutic target for treating RA.